PENDAMPINGAN DIGITAL MARKETING HALAL BAGI LPNU-UMKM TANI SEJAHTERA DESA DUWET KABUPATEN MALANG - Hudriyah Mundzir; Sri Hudiarini; Astrifidha Rahma Amalia; M. Nanak Zakaria; Muhammad Akhlis Rizza; Rofiq Hamzah (Jurnal Pengabdian kepada Masyarakat, 2026)
This community service project aims to assist LPNU–UMKM Tani Sejahtera in improving the quality and marketing of organic fertilizer products made from goat manure through the implementation of halal-based digital marketing. UMKM Tani Sejahtera, which is engaged in processing goat manure into organic fertilizer, faces challenges in marketing, branding, and utilizing digital platforms. The service activities were carried out in three phases: preparation, implementation, and evaluation. During the preparation phase, intensive discussions were held to identify the main issues, while the implementation phase involved training on digital marketing, branding, and optimizing the use of social media and marketplaces. Additionally, product identity design emphasizing the halal aspect was carried out. The outcome of this mentoring includes increased understanding of digital marketing and branding, as well as strengthening production and sales capacity through digital platforms. The evaluation shows an increase in the motivation and understanding of the partners in utilizing digital marketing. It is expected that this program will continue to support the sustainability of the UMKM business and encourage them to optimize existing potential, expand markets, and improve their product competitiveness in broader markets.